2005
DOI: 10.1200/jco.2005.03.158
|View full text |Cite
|
Sign up to set email alerts
|

Immunization With Mutantp53- andK-ras–Derived Peptides in Cancer Patients: Immune Response and Clinical Outcome

Abstract: A B S T R A C T PurposeTo determine the ability to induce tumor-specific immunity with individual mutant K-ras-or p53-derived peptides and to monitor clinical outcome. Patients and MethodsPatients in varying stages of disease underwent genetic analysis for mutations in K-ras and p53. Thirty-nine patients were enrolled. Seventeen-mer peptides were custom synthesized to the corresponding mutation. Baseline immunity was assessed for cytotoxic T-lymphocyte (CTL) response and interferon gamma (IFN-␥) release from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(92 citation statements)
references
References 39 publications
1
91
0
Order By: Relevance
“…Previous studies have shown that CD4 + T-cell immunity to position 12 mutated Ras (muRas) can be detected in the majority of patients with pancreatic cancer (3,5). The proof of this T-cell response and the early presence of muRas in the tumoral process have prompted the implementation of clinical trials aimed at inducing CTL responses against defined muRas antigens (9)(10)(11). In these studies, immunizations with peptides of 13 to 17 amino acids in length were able to induce CD4 + and CD8 + T lymphocytes specific for muRas.…”
mentioning
confidence: 99%
“…Previous studies have shown that CD4 + T-cell immunity to position 12 mutated Ras (muRas) can be detected in the majority of patients with pancreatic cancer (3,5). The proof of this T-cell response and the early presence of muRas in the tumoral process have prompted the implementation of clinical trials aimed at inducing CTL responses against defined muRas antigens (9)(10)(11). In these studies, immunizations with peptides of 13 to 17 amino acids in length were able to induce CD4 + and CD8 + T lymphocytes specific for muRas.…”
mentioning
confidence: 99%
“…25 The study was done independently of the subjects' HLA Class I and Class II haplotypes. The tumor of 1 of the subjects expressed the p53 Y220C mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination of cancer patients requires a target which would be present exclusively in cancer cells. Carbone et al [33] demonstrated prolonged survival of cancer patients (including lung cancer), which were immunized with cellular vaccine containing mutant p53 and KRASderived peptides.…”
Section: Kirsten-rous Avian Sarcoma (Kras)mentioning
confidence: 99%